2023
DOI: 10.1111/pce.14613
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paths of plant host toxicity are associated with the fungal toxin cercosporin

Abstract: The Cercospora species of fungi are responsible for leaf spot disease affecting many key economic crops. Most of these fungi secrete a toxic photodynamic molecule, cercosporin, that reacts with light and oxygen to produce reactive singlet oxygen ( 1 O 2 ) contributing to fungal virulence. We show similar cellular localization and aetiology of cercosporin in the non-host Arabidopsis and the host Nicotiana benthamiana. Cercosporin accumulates in cell membranes in an oxidized state and in plastids in a mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…SO is known to regulate PCD in abiotic stress responses (Laloi & Havaux, 2015), and this capability merits further investigation in the context of phototoxin production and biotic interactions. Furthermore, while plants may utilize SO-generating phototoxins for defense, there is also evidence that certain necrotrophic pathogens produce Type II phototoxins such as cercosporin and DHN-melanin that act as virulence factors (Beltrán-García et al, 2014;Koh et al, 2023). The fungal toxin cercosporin, for example, changes leaf conductance by permeabilizing guard cell membranes, inhibits photosynthesis, directly oxidizes host RNA and triggers SO-associated transcript profiles (Koh et al, 2023).…”
Section: So Production By Endogenous Photosensitizers In Plant Biotic...mentioning
confidence: 99%
See 1 more Smart Citation
“…SO is known to regulate PCD in abiotic stress responses (Laloi & Havaux, 2015), and this capability merits further investigation in the context of phototoxin production and biotic interactions. Furthermore, while plants may utilize SO-generating phototoxins for defense, there is also evidence that certain necrotrophic pathogens produce Type II phototoxins such as cercosporin and DHN-melanin that act as virulence factors (Beltrán-García et al, 2014;Koh et al, 2023). The fungal toxin cercosporin, for example, changes leaf conductance by permeabilizing guard cell membranes, inhibits photosynthesis, directly oxidizes host RNA and triggers SO-associated transcript profiles (Koh et al, 2023).…”
Section: So Production By Endogenous Photosensitizers In Plant Biotic...mentioning
confidence: 99%
“…Furthermore, while plants may utilize SO-generating phototoxins for defense, there is also evidence that certain necrotrophic pathogens produce Type II phototoxins such as cercosporin and DHN-melanin that act as virulence factors (Beltrán-García et al, 2014;Koh et al, 2023). The fungal toxin cercosporin, for example, changes leaf conductance by permeabilizing guard cell membranes, inhibits photosynthesis, directly oxidizes host RNA and triggers SO-associated transcript profiles (Koh et al, 2023). This light-dependent damage causes cell death and foliar lesions in the host plant, facilitating the infection process by necrotrophic fungi in the genus Cercospora (Santos Rezende et al, 2020).…”
Section: So Production By Endogenous Photosensitizers In Plant Biotic...mentioning
confidence: 99%
“…SO is known to regulate PCD in abiotic stress responses (Laloi & Havaux, 2015), and this capability merits further investigation in the context of phototoxin production and biotic interactions. Furthermore, while plants may utilize SO-generating phototoxins for defense, there is also evidence that certain necrotrophic pathogens produce Type II phototoxins such as cercosporin and DHN-melanin that act as virulence factors (Beltran-Garcia et al, 2014;Koh et al, 2023). The fungal toxin cercosporin, for example, changes leaf conductance by permeabilizing guard cell membranes, inhibits photosynthesis, directly oxidizes host RNA, and triggers SO-associated transcript profiles (Koh et al, 2023).…”
Section: So Production By Photosensitizers In Plant Biotic Interactionsmentioning
confidence: 99%
“…Furthermore, while plants may utilize SO-generating phototoxins for defense, there is also evidence that certain necrotrophic pathogens produce Type II phototoxins such as cercosporin and DHN-melanin that act as virulence factors (Beltran-Garcia et al, 2014;Koh et al, 2023). The fungal toxin cercosporin, for example, changes leaf conductance by permeabilizing guard cell membranes, inhibits photosynthesis, directly oxidizes host RNA, and triggers SO-associated transcript profiles (Koh et al, 2023). This light-dependent damage causes cell death and foliar lesions in the host plant, facilitating the infection process by necrotrophic fungi in the genus Cercospora (Rezende et al, 2020).…”
Section: So Production By Photosensitizers In Plant Biotic Interactionsmentioning
confidence: 99%
“…These abiotic stresses include dryness, salinity, injury, and in certain conditions exposure to high light. A common link between them was found to be singlet oxygen-generated perturbations in mRNA translation that is brought about by direct singlet oxygen oxidation of RNA (Koh et al, 2023(Koh et al, , 2021. It was shown that guanosine residues in mRNA are readily and specifically oxidized to 8-hydroxyguanosine that blocks consecutive mRNA translation.…”
Section: Introductionmentioning
confidence: 99%